Demigods Class Struggle in Rick Riordans The Sea of Monsters - Hafidhotul Husna; MUCH. KOIRI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2018)
Class struggle commonly happens in a society as a form of defense by particular group of people. Usually, they are minority people who have different view or ownership compared to the rests and put an effort to erase inequality they get from society by creating a movement to flip majority’s dominance. This study describes class struggle which is done by some of demigods in the half-blood camp and the effort which is taken by Luke’s party (Kronos’ alliances) and Percy’s party (Olympian defenders) in the novel The Sea of Monsters. Applying Social Class concept of Max Weber in general, this research is also supported by other concepts such as Greek Gods, inequality, and Weberian Stratification in particular. Yet, this study is still covered by sociological criticism as the research methodology. The result shows that class struggle which occurs in the novel is affected by inequality due to humanization and absolute authority of the Gods and Goddesses and Kronos’ whisper to influence the betraying demigods so that they shatter Olympian and help his resurgence to rule the world. However, class struggle movement does not only involve Luke’s party only, but Percy’s party also joins this movement to defense Olympians and mankind.